Characterizing Microchannel Plates for X-ray Detection and Imaging - H, Golnabi; P, Kamyar; H, Ahmadi (Malaysian Journal of Science, 2002)
The goal here is to characterize crucial parameters involved in design and operation of such devices as detectors and also position sensitive detectors for X-ray detection and imaging. For example, MCP gain, dark noise, quantum efficiency, and image readouts for MCP X-ray detectors are discussed. In the case of MCP, we consider parameters affecting the linear and saturated operation of the device. Gain fatigue and gain desperation at high count rates are described and optimum conditions are explained for the case of MCP soft X-ray detectors. The geometrical probability functions that provide optimum quantum detection efficiency are described in this study. A limitation of a channel multiplier is the surface area of the entrances to the channel, which is usually less than the surface area of the entrance plate. For this reason, MCPs with the circular, square, and hexagonal channels are examined in this work. The geometrical efficiency for detecting hard X-rays as a function of the wall thickness for different thickness values is presented in this study. The geometrical efficiency as a function of the open width, d, for different L values is also investigated. The obtained results show that for each thickness value there exists an optimum opening diameter value for a given channel thickness and photon energy. Microchannel plates based on the position sensing technique are also described in this study.